Effects of External Pressure on Venous Vessels in the Human Body - Khurramov , Bekhruz; Xasanov , Azizbek; Xolov , Sunnat (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
External pressure applied to venous blood vessels significantly influences venous compliance, transmural pressure, and overall hemodynamics. Due to their thin walls and low intravascular pressure, veins are particularly sensitive to external mechanical forces. This scientific article analyzes the physiological mechanisms through which external pressure affects venous blood flow, venous return, and microcirculation. Both therapeutic and pathological effects of compression are discussed, highlighting clinical applications as well as potential risks associated with excessive pressure.